Intensification of biobutanol production in batch oscillatory baffled bioreactor - N., Masngut; Harvey, Adam. P. (Elsevier BV, 2012)
A novel intensified bioreactor called the oscillatory baffled bioreactor (OBB) was evaluated for biobutanol production. Batch acetone-butanol-ethanol (ABE) fermentations were conducted in OBB at various oscillatory Reynolds numbers (0-1870) and in stirred tank reactors (STR) at various stirrer speeds (0-200 rpm). The fermentations were performed anaerobically using clostridia strain Clostridium GBL1082 at constant temperature. In the OBB, the highest ABE yield achieved was 0.35 g/g (of g ABE produced/g glucose used), which was comparable to yield achieved in the STR. The highest productivity achieved in the OBB was 0.22 g/L-hr, 38% higher than the maximum achieved in the STR. The use of the highest mixing intensities (for both OBB and STR) within the studied range resulted in higher acid concentration, suggesting that acids were not reassimilated efficiently. There was a balance between achieving uniform suspension of the bio-fluid and the adverse effects of shear in both bioreactors. This is an abstract of a paper presented at the CHISA 2012 - 20th International Congress of Chemical and Process Engineering and PRES 2012 - 15th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (Prague, Czech Republic 8/25-29/2012).